Modern Advancements in Post-Detonation Nuclear Forensic Analysis - S. Adam Stratz; Jonathan A Gill; John D. Auxier II; Howard L. Hall (International Journal of Nuclear Security, 2016)
Deterring nuclear terrorism is a critical national asset to support the preclusion of non-state actors from initiating a nuclear attack on the United States. Successful attribution of a detonated nuclear weapon allows for timely responsive measures that prove essential in the period following a nuclear event. In conjunction with intelligence and law enforcement evidence, the technical nuclear forensics (TNF) post-detonation community supports this mission through the development and advancement of expertise to characterize weapon debris through a rapid, accurate, and detailed approach. Though the TNF field is young, numerous strides have been made in recent years toward a more robust characterization capability. This work presents modern advancements in post-detonation expertise over the last ten years and demonstrates the need for continued extensive research in this field.
Keywords: Nuclear Forensics; Post-Detonation; Nuclear Security